Chemical Composition and Pharmacological Effects of Geopropolis Produced by Melipona quadrifasciata anthidioides. (26th October 2017) - dos Santos, Cintia Miranda; Campos, Jaqueline Ferreira; dos Santos, Helder Freitas; Balestieri, José Benedito Perrella; Silva, Denise Brentan; de Picoli Souza, Kely; Carollo, Carlos Alexandre; Estevinho, Leticia M.; dos Santos, Edson Lucas
Abstract : Stingless bees produce geopropolis, which is popularly described for its medicinal properties, but for which few scientific studies have demonstrated pharmacological effects. The objective of this study was to investigate the chemical composition of the geopropolis of Melipona quadrifasciata anthidioides and to evaluate its antioxidant, antimutagenic, anti-inflammatory, and antimicrobial activities. The composition of the hydroethanolic extract of geopropolis (HEG) included di- and trigalloyl and phenylpropanyl heteroside derivatives, flavanones, diterpenes, and triterpenes. HEG showed antioxidant action via the direct capture of free radicals and by inhibiting the levels of oxidative hemolysis and malondialdehyde in human erythrocytes under oxidative stress. HEG also reduced the frequency of gene conversion and the number of mutant colonies of S. cerevisiae . The anti-inflammatory action of HEG was demonstrated by the inhibition of hyaluronidase enzyme activity. In addition, HEG induced cell death in all evaluated gram-positive bacteria, gram-negative bacteria, and yeasts, including clinical isolates with antimicrobial drug resistance. Collectively, these results demonstrate the potential of M. q. anthidioides geopropolis for the prevention and treatment of various diseases related to oxidative stress, mutagenesis, inflammatory processes, and microbial infections.